HISTORY OF MASTER’S AND DOCTORAL DEGREE TRAINING FROM 1965-2013 IN BRAZIL: A MAP OF THE PUBLIC EDUCATION SERVICE IN THE POSTGRADUATE SYSTEM - Dotta, Alexandre Godoy; Neves, Ozias Paese (European Scientific Journal, ESJ, 2015)
This article presents a historical map of the political structure and the financing model of the postgraduate system stricto sensu in Brazil. It offers a historical analysis based on the study of the National Plan for Postgraduate Education 2011-2020, whose primary objective is to foster the development of the public service of higher education in Brazil. This article presents a history of the numbers of doctorates and master’s degrees granted in Brazil from 1960 to 2013. It emphasizes the central role of the Coordination for the Improvement of Higher Education Personnel (CAPES) in structuring public policy for the postgraduate system. Finally, it assesses the number of scholarships provided by past governments and establishes a comparative perspective on the investment in Brazilian postgraduate education.